Patients with deliberate self-harm attended in emergency setting at a tertiary care hospital: A 13-month analysis of clinical-psychiatric profile. (November 2019) - Singh, Swarndeep; Kumar, Saurabh; Deep, Raman
Objectives: To describe the pattern and clinical-psychiatric profile of patients presenting with deliberate self-harm attempt to an emergency setting. Methods: The study involves the analysis of the case records of 109 consecutive patients with deliberate self-harm evaluated by the psychiatric emergency team at a premier, tertiary care hospital in India over a period of 13 months (January 2015–January 2016). Results: Deliberate self-harm had a clinical prevalence of 16.4% (109/666) among total mental and behavioral emergencies attended in the same period. A large majority of attempters were in the age range of 18–39 years (84.4%), and females (58.7%) outnumbered males in total sample. Married females and unmarried males had significantly higher chances of attempting deliberate self-harm (χ 2 = 6.57, p = 0.01). More than half (52.3%) of patients were found to have a diagnosable psychiatric illness at the time of presentation, most common being depressive disorder in 19.3% of overall sample. Past history of a psychiatric illness was evident in only 12.5% of patients. Common methods of deliberate self-harm were prescription drug/psychotropic overdose, poisoning with ingestion of phenyl cleaner or rat-killer poison. Significant gender differences were observed in the nature of precipitating events for deliberate self-harm, with interpersonal relationship problems being significantly more common in women (p = 0.03). Conclusion: This study adds relevant and useful information on cross-cutting as well as gender-specific characteristics of patients presenting with deliberate self-harm attempt, from a developing country context. The study findings bear implications for designing interventions for primary and secondary prevention of such behavioral emergencies at a community level.